Charged pore-lining residues are required for normal channel kinetics in the eukaryotic mechanosensitive ion channel MSL1. Issue 1 (1st January 2020) - Schlegel, Angela M.; Haswell, Elizabeth S.
ABSTRACT: Mechanosensitive (MS) ion channels are widespread mechanisms for cellular mechanosensation that can be directly activated by increasing membrane tension. The well-studied MscS family of MS ion channels is found in bacteria, archaea, and plants. MscS-Like (MSL)1 is localized to the inner mitochondrial membrane of Arabidopsis thaliana, where it is required for normal mitochondrial responses to oxidative stress. Like Escherichia coli MscS, MSL1 has a pore-lining helix that is kinked. However, in MSL1 this kink is comprised of two charged pore-lining residues, R326 and D327. Using single-channel patch-clamp electrophysiology in E. coli, we show that altering the size and charge of R326 and D327 leads to dramatic changes in channel kinetics. Modest changes in gating pressure were also observed while no effects on channel rectification or conductance were detected. MSL1 channel variants had differing physiological function in E. coli hypoosmotic shock assays, without clear correlation between function and particular channel characteristics. Taken together, these results demonstrate that altering pore-lining residue charge and size disrupts normal channel state stability and gating transitions, and led us to propose the "sweet spot" model. In this model, the transition to the closed state is facilitated by attraction between R326 and D327 and repulsion between R326 residues of neighboring monomers. In the open state, expansion of the channel reduces inter-monomeric repulsion, rendering open state stability influenced mainly by attractive forces. This work provides insight into how unique charge-charge interactions can be combined with an otherwise conserved structural feature to help modulate MS channel function.